Acute-onset paralytic strabismus in toddlers is important to consider as a potential early sign of late-infantile Metachromatic Leukodystrophy. (March 2022) - Beerepoot, Shanice; Wolf, Nicole I.; Wehner, Katharina; Bender, Benjamin; van der Knaap, Marjo S.; Krägeloh-Mann, Ingeborg; Groeschel, Samuel
Abstract: Objectives: Metachromatic leukodystrophy (MLD) is a fatal lysosomal storage disease characterized by progressive demyelination within the central and peripheral nervous system. Rapid diagnosis is crucial in view of evolving therapeutic options. Strabismus has anecdotally been described as a feature in children with MLD. Our first aim was to examine the prevalence of strabismus as an early or even presenting sign of MLD in two nationwide cohorts. Second, we aimed to investigate the temporal relation between the onset of strabismus and gross motor deterioration, other early onset eye movement disorders and brain white matter abnormalities. Methods: Clinical records of 204 MLD patients at the University Children's Hospital Tubingen and Amsterdam University Medical Center were reviewed on the presence of strabismus and other eye movement disorders. Gross motor deterioration and white matter abnormalities on brain MRI were evaluated by using the Gross Motor Function Classification in MLD and MLD LOES score, respectively. Results: We identified strabismus as an early sign in MLD patients with the late-infantile form, with a prevalence of 27% (N = 17). The onset of strabismus preceded gross motor symptoms and brain white matter abnormalities in 71% and 46% respectively of the cases. Important characteristics were an acute-onset paralytic esotropia, partly accompanied by other eye movement abnormalities, and gadolinium enhancement of the cranial nerves. Conclusions: Acute-onset paralytic strabismus in toddlers should be considered a potential early sign of late-infantile MLD and might result from early cranial nerve involvement. Brain MRI with gadolinium contrast may facilitate early diagnosis. Highlights: Acute-onset paralytic strabismus can be a potential early clinical sign of MLD. The prevalence of strabismus as an early sign in late-infantile MLD patients is 27%. Strabismus preceded gross motor symptoms in 71% of the identified cases. Strabismus preceded white matter abnormalities on brain MRI in 46% of the cases. Strabismus in late-infantile MLD might result from early cranial nerve involvement.